2020
DOI: 10.1152/ajplung.00065.2019
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage: necroptosis in the development of lung injury

Abstract: Cell death is increasingly recognized as a driving factor in the development of acute lung injury. Necroptosis, an immunogenic regulated cell death program important in innate immunity, has been implicated in the development of lung injury in a diverse range of conditions. Characterized by lytic cell death and consequent extracellular release of endogenous inflammatory mediators, necroptosis can be both beneficial and deleterious to the host, depending on the context. Here, we review recent investigations link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…Pyroptosis and necroptosis of alveolar epithelial and endothelial cells are major elements in development and progression of ARDS in part by releasing high mobility group box 1 (HMBG1) and other inflammatory damage-associated molecular patterns (DAMPs) [ [89] , [90] , [91] ]. Hence, the pyroptotic death of type 2 alveolar cells following SARS-Cov2 infection may also be of pathophysiological significance in the development of COVID-19 and a major source of inflammation [ 85 , 86 ].…”
Section: Activation Of Alveolar Epithelial Cells and Macrophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Pyroptosis and necroptosis of alveolar epithelial and endothelial cells are major elements in development and progression of ARDS in part by releasing high mobility group box 1 (HMBG1) and other inflammatory damage-associated molecular patterns (DAMPs) [ [89] , [90] , [91] ]. Hence, the pyroptotic death of type 2 alveolar cells following SARS-Cov2 infection may also be of pathophysiological significance in the development of COVID-19 and a major source of inflammation [ 85 , 86 ].…”
Section: Activation Of Alveolar Epithelial Cells and Macrophagesmentioning
confidence: 99%
“…As previously discussed, pyroptosis and necroptosis of alveolar epithelial and endothelial cells are major elements in the development and progression of ARDS [ [89] , [90] , [91] ]. There is also evidence to suggest that the pyroptotic death of neutrophils makes an independent contribution to the exacerbation of inflammation in more advanced stages of the condition [ 203 ].…”
Section: The Recruitment Of Activated Neutrophils Into Alveolae and Imentioning
confidence: 99%
See 2 more Smart Citations
“…Shashaty et al demonstrated that among patients with sepsis or trauma, the change in plasma RIPK-3 levels 48 h after admission was independently associated with ARDS [3]. Because RIPK-3 mediates not only necroptosis but also other inflammatory pathways [2], the elevation of RIPK-3 does not directly indicate the execution of necroptosis. To confirm the role of RIPK-3 in COVID-19-ARDS patients, further studies are needed including a larger number of participants and histological evaluation of lung tissues, especially since RIPK-3-mediated necroptosis could be a potential therapeutic target for COVID-19-related ARDS.…”
Section: Dear Editormentioning
confidence: 99%